Advanced literacy practices from the clinic to the classroom - Ortlieb, Evan.; Cheek, Earl H. (Bingley, U.K. : Emerald, 2013)
Advanced Literacy Practices: From the Clinic to the Classroom includes salient information about clinical literacy practices that transfer to other settings. From historical perspectives to cutting edge instructional techniques, this edited text includes elements of designing literacy clinics, models of reading and writing practices, technology-based instruction, and frameworks for meeting the diverse needs of students. As the second volume in the series, Literacy Research, Practice, and Evaluation, notable authors share their perspectives as effective literacy clinic directors of how to enhance the literacy achievement of students. These first-hand accounts are critical as readers glean from their career-long devotion and decades of research, practice, and experimentation. Readers garner rich perspectives on literacy improvement through this research-based practical guide. It provides a current examination of issues and trends in clinical literacy practices appropriate for novice and experienced educators and researchers alike.
A historical view of student learning and teacher development in reading clinics / B.P. Laster -- Creating a university-based literacy center / Debra Coffey ... [et al.] -- Designing an off-campus literacy clinic / Tammy Ryan -- Coaching for success : UCF enrichment programs in literacy / Michelle Kelley, Taylar Wenzel -- Creating an optimal learning environment for struggling readers / Rose Marie Codling -- Vocabulary/comprehension-based models of reading clinics / Evan Ortlieb, Wolfram Verlaan, Earl H. Cheek -- When kids can't read, what a focus on fluency can do : The reading clinic experience at Kent State University / Belinda Zimmerman, Timothy Rasinski, Maria Melewski -- Building writing communities and partnering with families : multiple perspectives from a writing practicum / Cheryl Dozier, Julie Smit -- Preparing special educators to teach reading : a pre-student teaching practicum / Mary Anne Prater, Nari Carter, JoAnn Munk -- Transfer and transformation of knowledge and practices from literacy clinic to community / Stephanie L. McAndrews, Shadrack G. Msengi -- Preparing preservice teachers to differentiate instruction for linguistically diverse students in urban classrooms / Patricia Paugh, Mary Brady -- Taking technology from clinic to classroom / Lee Ann Tysseling, B.P. Laster -- Providing a 'pocket tutor' : enhancing metacognition through podcasted comprehension prompts / Erica Bowers ... [et al.] -- Innovative practices in the reading clinic : helping 'digital natives' incorporate 21st century technologies / Joan A. Rhodes -- Supporting struggling readers and literacy clinicians through reflective video pedagogy / Lynn E. Shanahan ... [et al.] -- The gradual increase of responsibility model : mentoring for improved intervention / Vicki Collet -- Peer conferencing : adding a collaborative component to graduate and undergraduate university reading clinics / Sherrye Dee Garrett, Lucinda Marie Juarez -- Keeping learners at the center of teaching / Cheryl Dozier, Theresa Deeney -- Innovative practices : developing effective collaboration and partnerships within school-based reading clinics / Tammy Milby.
Print version record
Keywords: Education -- Evaluation; Education -- Teaching Methods & Materials -- Reading & Phonics; Education -- Research; Literacy strategies; Teaching skills & techniques; Literacy; Literacy programs; Reading